Genome-wide association studies of salinity tolerance in local aman rice: GWAS of salinity tolerance in rice - Jahan, Nusrat; Raihan, Mohammad Sharif; Islam, M. Moshiul; Era, Farzana Mustafa; Alalawy, Adel I.; Omran, Awatif M. E; Alanazi, Yasmene F.; Sakran, Mohamed; Alasmari, Abdulrahman; Alzuaibr, Fahad M.; El Sabagh, Ayman; Kahrizi, Danial; et al. (Cellular and Molecular Biology, 2024)
The present study aimed to identify and characterize new sources of salt tolerance among 94 rice varieties from varied geographic origins. The genotypes were divided into five groups based on their morphological characteristics at both vegetative and reproductive stages using salinity scores from the Standard Evaluation System (SES). The experiment was designed as per CRD (Completely Randomized Design) with 2 sets of salinity treatments for 8 dS/meter and 12 dS/meter, respectively compared with one non-salinized control set. Using a Soil Plant Analysis Development (SPAD) meter, assessments of the apparent chlorophyll content (greenness) of the genotypes were done to comprehend the mechanism underlying their salt tolerance. To evaluate molecular genetic diversity, a panel of 1 K RiCA SNP markers was employed. Utilizing TASSEL 5.0 software, 598 filtered SNPs were used for molecular analysis. Whole-genome association studies (GWAS) were also used to investigate panicle number per plant (pn, tiller number per plant (till), SPAD value (spad), sterility (percent) (str), plant height (ph) and panicle length (pl. It is noteworthy that these characteristics oversee conveying the visible signs of salt damage in rice. Based on genotype data, diversity analysis divided the germplasm groups into four distinct clusters (I, II, III and IV). For the traits studied, thirteen significant marker-trait associations were discovered. According to the phenotypic screening, seven germplasm genotypes namely Koijuri, Asha, Kajal, Kaliboro, Hanumanjata, Akundi and Dular, are highly tolerant to salinity stress. The greenness of these genotypes was found to be more stable over time, indicating that these genotypes are more resistant to stress. Regarding their tolerance levels, the GWAS analysis produced comparable results, supporting that salinity-tolerant genotypes having minor alleles in significant SNP positions showed more greenness during the stress period. The Manhattan plot demonstrated that at the designated significant SNP position, the highly tolerant genotypes shared common alleles. These genotypes could therefore be seen as important genomic resources for accelerating the development and release of rice varieties that are tolerant to salinity.